2015
DOI: 10.7205/milmed-d-14-00625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiac Surgery on Duty Status in the Active Duty Military Population

Abstract: No modern studies have addressed the impact of cardiac surgery on military duty status, which is associated with constraints not applicable to the general population. A review of all active duty patients undergoing coronary artery bypass grafting (CABG), mitral valve repair (MVrep), bioprosthetic valve replacement (BIOVALVE), mechanical valve replacement (MECHVALVE), and septal defect closure (ASD/VSD) at Naval Medical Center Portsmouth between January 1, 2004 and December 31, 2011 was used to determine final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…This may be due to increased life stressors even among people. This result is in accordance with Leathy &Jada(2015) (18) , who revealed that average age of the studied sample was 40 (range 20-55). Moreover a study conducted by Amaal F et al, (2017) (19) revealed that the average age of the studied sample wasranged between 50 and 59 years with a mean age of (45.9±11.7).…”
Section: Regarding To Demographicsupporting
confidence: 92%
“…This may be due to increased life stressors even among people. This result is in accordance with Leathy &Jada(2015) (18) , who revealed that average age of the studied sample was 40 (range 20-55). Moreover a study conducted by Amaal F et al, (2017) (19) revealed that the average age of the studied sample wasranged between 50 and 59 years with a mean age of (45.9±11.7).…”
Section: Regarding To Demographicsupporting
confidence: 92%
“…The present study included articles originating from Europe ( n = 29) [23, 24, 26–30, 32–34, 36, 38, 40, 44, 45, 47, 50–54, 56, 58–60, 62–65], USA ( n = 10) [25, 31, 35, 37, 41, 42, 46, 57, 67, 68], Australia ( n = 3) [55, 61, 66], Iran ( n = 2) [39, 43] and Israel ( n = 1) [49].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 papers included in this review, the majority (n = 44) employed quantitative research, whereas one used a mixed-method design. The study designs were eight registry studies [23][24][25][26][27][28][29][30], seven clinical trials (six randomised trials and one non-randomised) [31][32][33][34][35][36][37], 18 cohort studies (15 prospective studies and three retrospective studies) [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], one mixed-method study [56], two case-control studies [57,58] and nine cross-sectional studies (three surveys and six crosssectional studies) [59][60][61][62][63][64][65][66][67].…”
Section: Setting and Samplementioning
confidence: 99%
“…Also, a study conducted by Ahmed et al,(2017) (23) revealed that the average age of the studied sample ranged between 50 and 59 years with a mean age of (45.9±11.7) However, Abd El-gafour et al, (2021) (24) in a study about "assessment of patients' needs pre and post open heart surgery" revealed that less than half of the studied patients ranged between 50-60 years. Moreover, Leahy et al, (2015) (25) revealed Vol. 31.…”
Section: Discussionmentioning
confidence: 99%